E-Commerce untuk Mendukung Business to Business Menggunakan Dynamic Dbmss: Studi Kasus pada Perusahaan Dagang Cross Tech - Subekti, Mohammad; Tandiono, Anthoni; Tania, Fenky; A., Hendro Wibowo (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The purpose of this study is to develop an e-commerce that can distribute any information about the products of PD Cross Tech. The e-commerce is supported by dynamic DBMS and can be connected via database reseller server so that it can do information sharing. The distribution is performed using the Distributed Relational Database Management System (DRDBMS), supported by the File Transfer Protocol and Virtual Private Network. In other words the e-Commerce supports multiplatform database. Research methodologies used are analytical methods, design methods, and literature study. Results showed that PD Cross Tech needs a new e-Commerce that supports multiplatform database. With this e-Commerce, it is expected that similar computer equipment needs for many organization in Indonesia can be designed in the same way.